2017
DOI: 10.24326/asphc.2017.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenating Older Apple Trees by Root Pruning Combined With Arbuscular Mycorrhizal Fungi

Abstract: Older apple trees often demonstrate physiologically unreasonable shoot distribution due to root system aging, which results in lower fruit yield and poor fruit quality. Therefore this study was conducted to test whether root pruning combined with arbuscular mycorrhizal fungi could restore growth potential of fortyyear-old Red Fuji apple trees (Malus × domestica Borkh.) in a commercial orchard in 2013, by root pruning along both sides of rows, 80 cm from the trunk, to a depth of 30 cm and application of 100 ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…At present, the management of aged orchards is mainly focused on two aspects: the transformation (such as grafting, pruning and soil improvement) and renewal of aged orchards (Ma et al, 2018). Although pruning and grafting are currently recognized as effective methods for the rejuvenation of aged orchards in the short term, the decreasing soil quality around the roots in aged orchards is no longer suitable for root growth and maintaining a large output of fruit trees (Zhang et al, 2017). Furthermore, the renewal of aged orchards is time-and cost-consuming, but also causes problems, such as apple replant disease, as a result of poor soil conditions (Winkelmann et al, 2019).…”
Section: Effects Of Biofertilizer On the Aged Apple Orchardsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the management of aged orchards is mainly focused on two aspects: the transformation (such as grafting, pruning and soil improvement) and renewal of aged orchards (Ma et al, 2018). Although pruning and grafting are currently recognized as effective methods for the rejuvenation of aged orchards in the short term, the decreasing soil quality around the roots in aged orchards is no longer suitable for root growth and maintaining a large output of fruit trees (Zhang et al, 2017). Furthermore, the renewal of aged orchards is time-and cost-consuming, but also causes problems, such as apple replant disease, as a result of poor soil conditions (Winkelmann et al, 2019).…”
Section: Effects Of Biofertilizer On the Aged Apple Orchardsmentioning
confidence: 99%
“…The 9# orchard where biofertilizer had been applied also had a reduced abundance of plant pathogens causing apple replant disease and black spot, such as Pseudonymnoscus (Mao et al, 2017), Cylindrocarpon (Wang, 2018;Yin et al, 2017), Sarocladium (Hou, 2016) and Pyrenopeziza (Gilles et al, 2001;Oxley & Walters, 2012) (Figures 5, 6, S1 and S2). In other studies, Zhang et al (2017) reported that arbuscular mycorrhizal fungi (AMF) played a major role in the enhancement of the tree vigour in aged orchards, which could offset the loss of roots based on their greater hyphal network. Yang et al (2014) also found that Glomus versiforme colonization of older apple plants markedly increased mineral nutrient concentrations in apple leaves, especially those of nitrogen and phosphorus.…”
Section: Effects Of Biofertilizer On the Aged Apple Orchardsmentioning
confidence: 99%